Inhibition of Corneal Neovascularization by Topically Administered Propranolol in a Rabbit Model - Kasiri, Ali (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: To evaluate the effects of topical propranolol for treatment of the corneal neovascularization (CNV) in a rabbit model of corneal injury. Methods: The CNV model was induced by 3 sutures of the cornea in 20 rabbits (20 corneas). 2 weeks after CNV, all sutures were removed then rabbits were divided randomly into two groups: Groups 1 received topical propranolol 10 mg/mL and Group 2 received only topical normal saline drops as control group, in the right eyes three times a day for 2 weeks. Photographs of (CNV) were obtained before drug administration and at 1 and 2 weeks after therapy. The images were analyzed using NIH Image J1.49c software. Results: The mean percentage of CNV area estimated as 100% before treatment. At the 1 week after treatment, the mean percentage of NV area in propranolol and saline group were 78.01 ± 4.16 and 93.33 ± 4.57, respectively. Moreover, at the 2 weeks after treatment were 65.72 ± 4.15 and 84.96 ± 5.21, respectively. After 1 and 2 weeks treatment, the NV area in propranolol group was regressed more than saline group significantly (P < 0.0001). Conclusion: Topical administration of propranolol reduces CNV in the short-term, but the efficacy of long-term treatment needs more investigations.